Urban governance of disease - Rebecca Katz; Sangeeta Mookherji; Morgan Kaminski; Vibhuti Haté; Julie E. Fischer (Administrative Sciences, 2012)
Rapid population growth, urbanization, and the growing challenges faced by the urban poor require redefining the paradigm for public health interventions in the 21st century, creating new approaches that take urban determinants of health into consideration. The widening disparity between the urban poor and the urban rich further exacerbates health inequities. Existing tools for global governance of urban health risks fall short, particularly in the lack of formal mechanisms to strengthen collaboration and communication among national and municipal agencies and between their local and international non-governmental partners. There is also a clear disconnect between governance strategies crafted at the international level and implementation on the ground. The challenge is to find common ground for global goods and municipal needs, and to craft innovative and dynamic policy solutions that can benefit some of the poorest citizens of the global urban network.
Keywords: 350; global health governance; urban health governance; poverty; urbanization